Thermoluminescence characteristics of the irradiated minerals extracted from red pepper (Capsicum annuum L.) spice - Marcazzo, Salvador Julian (2012)
The inorganic polymineral content in the foodstuffs allows to analyze the main thermoluminescence (TL) characteristics that may be useful in the identification of irradiated food. The mineral fraction was separated from commercial Mexican red pepper (Capsicum annuum L.). X-ray diffraction shows that the mineral composition of the samples was mainly quartz. From the mineral fraction of different grain sizes, samples of 149 ¹m were selected for this study because of the high TL signals. The samples were irradiated from 1 to 500 Gy by using a 60Co irradiator. The TL characteristics like glow curve shape, dose-response, UV and sunlight bleaching and fading were analyzed. The glow curves show an intense TL peak at 82 ±C followed by others with less intensity at 130, 170 and 340 ±C. The TM-TSTOP method shows six TL glow peaks that was taken into account for calculation the activation energies values. Because the complex structure of the glow curves, the kinetics parameters were determined by using a computerized deconvolution program assuming the general order kinetics model.